Safety profile of solid lipid nanoparticles loaded with rosmarinic acid for oral use: in vitro and animal approaches - Madureira, Ana Raquel (2016)
Rosmarinic acid (RA) possesses several protective bioactivities that have attracted increasing interest by nutraceutical/pharmaceutical industries. Considering the reduced bioavailability after oral use, effective (and safe) delivery systems are crucial to protect RA from gastrointestinal degradation. This study aims to characterize the safety profile of solid lipid nanoparticles produced with Witepsol and Carnauba waxes and loaded with RA, using in vitro and in vivo approaches, focused on genotoxicity and cytotoxicity assays, redox status markers, hematological and biochemical profile, liver and kidney function, gut bacterial microbiota, and fecal fatty acids composition. Free RA and sage extract, empty nanoparticles, or nanoparticles loaded with RA or sage extract (0.15 and 1.5 mg/mL) were evaluated for cell (lymphocytes) viability, necrosis and apoptosis, and antioxidant/prooxidant effects upon DNA. Wistar rats were orally treated for 14 days with vehicle (control) and with Witepsol or Carnauba nanoparticles loaded with RA at 1 and 10 mg/kg body weight/d. Blood, urine, feces, and several tissues were collected for analysis. Free and loaded RA, at 0.15 mg/mL, presented a safe profile, while genotoxic potential was found for the higher dose (1.5 mg/mL), mainly by necrosis. Our data suggest that both types of nanoparticles are safe when loaded with moderate concentrations of RA, without in vitro genotoxicity and cytotoxicity and with an in vivo safety profile in rats orally treated, thus opening new avenues for use in nutraceutical applications.